Excitation of Large Axisymmetric Bodies by Magnetostrictive Ultrasonic Transducers - Vjuginova, Alena A.; Durukan, Yasemin; Novik, Alexander A. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2020)
Low-frequency power ultrasonic systems are used to increase productivity of different technological processes, in some cases it is necessary to provide ultrasonic excitation of large bodies by using of typical rod-type ultrasonic transducers. In this work method of ultrasonic excitation of large axisymmetric three-dimensional objects with sizes well over wavelength is proposed and investigated. Two rod-type magnetostrictive ultrasonic transducers with operating frequency 20 kHz are used for excitation of resonator operating in phase. Frequency properties and mode shapes of resonator construction vibrating in high-order radial modes are analyzed and optimized.